PROFIL PENYELESAIAN SOAL PADA MATERI LUAS PERMUKAAN KERUCUT OLEH SISWA KELAS IX SMP NEGERI 1 KASIMBAR: Profile for Solving HOTS Questions On The Cone Surface Area Material by Students of Class IX SMP Negeri 1 Kasimbar - Miranda, Dini; Hasbi, Muh.; Lefrida, Rita (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to profile the completion of HOTS questions on the conical surface area material by SMP Negeri 1 Kasimabar students based on differentiated cognitive levels. This type of research is qualitative research. The subjects of this study were 2 students of different genders taken from class IX SMP Negeri 1 Kasimbar. The research subjects were one student with high mathematics ability with female gender (LN), and one student with high mathematics ability with male gender (MS). The data collection techniques in this study were written tests and in-depth interviews. The test given to the research subjects was a HOTS problem test on cone surface area material at the cognitive level of analyzing (C4). The results of this study indicate that the profile of solving HOTS problems on the surface area of the cone by students with high mathematics ability LN at the cognitive level of analyzing is correct, because the subject can distinguish information, organize by creating a structure in systematic problem solving and attribute by making conclusions based on the information obtained very well. While the profile of HOTS problem solving of cone surface area by MS high mathematics ability students at the cognitive level of analyzing is good, because MS subjects are also able to distinguish information and organize by creating structures in systematic problem solving, it's just that at the stage of attributing MS subjects are still lacking, because at the stage of attributings